2019
DOI: 10.1186/s12931-019-0971-8
|View full text |Cite
|
Sign up to set email alerts
|

Breath biomarkers in idiopathic pulmonary fibrosis: a systematic review

Abstract: BackgroundExhaled biomarkers may be related to disease processes in idiopathic pulmonary fibrosis (IPF) however their clinical role remains unclear. We performed a systematic review to investigate whether breath biomarkers discriminate between patients with IPF and healthy controls. We also assessed correlation with lung function, ability to distinguish diagnostic subgroups and change in response to treatment.MethodsMEDLINE, EMBASE and Web of Science databases were searched. Study selection was limited to adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 116 publications
0
15
1
Order By: Relevance
“…The correlation between CaNO and TLCO% may result both by an impairment of alveolar diffusion and by the increase of NO production at alveolar levels, as demonstrated by Pullamssetti [20]. The reliability of CaNO were confirmed by a recent metanalysis in which CaNO emerged as the most promising of various breath biomarkers for clinical management of IPF [21].…”
Section: Discussionmentioning
confidence: 86%
“…The correlation between CaNO and TLCO% may result both by an impairment of alveolar diffusion and by the increase of NO production at alveolar levels, as demonstrated by Pullamssetti [20]. The reliability of CaNO were confirmed by a recent metanalysis in which CaNO emerged as the most promising of various breath biomarkers for clinical management of IPF [21].…”
Section: Discussionmentioning
confidence: 86%
“…Consequently, there is still a need for discriminative breathomics to diagnose and monitor ILDs. Until now, only two of such comprehensive breathomic studies have examined the excretion of disease-specific VOCs in ILDs [ 79 ]. In the first study in 2005, elevated level of ethane were reported to be exhaled in the breath of 34 ILD patients compared to the exhaled air of 16 healthy controls [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker research has been undertaken using peripheral blood, bronchoalveolar lavage fluid (BALF), and exhaled breath condensate (EBC) [11]. Numerous molecules involved in alveolar epithelial cell injury, proliferation and matrix remodeling as well as immune regulation have been proposed as potential biomarkers [10].…”
Section: Introductionmentioning
confidence: 99%